Pengaruh Elemen Spasial Wayfinding Terhadap User Experience Wisatawan Kampung Heritage Kayutangan - Amaylya, Madeina Annadwa (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2025)
Kampung Heritage Kayutangan is a rapidly growing thematic tourism village in Malang City. However, the spatial character of the village with its dense residential pattern and organically developed layout without formal planning may cause difficulties for tourists in understanding spatial orientation. This condition can impact the comfort and overall experience of visitors during exploration. It presents a challenge for tourism managers to ensure a comfortable environment that supports smooth tourist activities. The local tourism group known as POKDARWIS has taken steps to improve navigational ease by providing maps and directional signage throughout the kampung. However, these aids are not fully effective as some tourists still report feeling confused or even entering private residential areas. This indicates that current navigation tools do not entirely meet tourist’s needs for orientation. In practice, wayfinding involves a person’s interaction with spatial elements to build a mental map that guides their navigation. This study examines how spatial elements affect wayfinding behaviour and user experience. A quantitative method was applied using questionnaires distributed to 100 respondents and analyzed with SPSS. The results show that spatial elements significantly influence user experience, apart from that, wayfinding behavior also has an influence on user experience.